Accuracy of body mass prediction using segmental inertia parameters modelled from photographic images - Williams, G.; Irwin, G.; Kerwin, D. G.; Newell, K. M. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The aim of this study was to evaluate the accuracy between the measured and predicted body mass, using the methods of Gittoes et al. (2009), and investigate the relationship between mass and stature and this accuracy. Fifteen male, recreational athletes from a university`s sporting population took part in the study. Measured whole-body masses were compared with predicted whole-body masses calculated using photographic dimensional data and an inertia model. Mean absolute error between measured and predicted whole-body mass was 5.42 ± 2.92 %. A strong, negative correlation between measured whole-body mass and relative % error (r = -0.80) and a normalising value and relative % error was found. It is suggested that for similar participants errors could be up to ± 10% for participants with body masses much greater or less than 71 kg or normalising values equating to 1230 Nm.